ANALYSIS OF THE INFLUENCE OF FINANCIAL LITERACY ON PERSONAL FINANCIAL MANAGEMENT BEHAVIOR IN THE MILLENNIAL GENERATION - Bambang Hermawan; Didik Wahyudi (Adisam Publisher, 2025)
This research aims to analyze the influence of financial literacy on personal financial management behavior in the millennial generation. Using literature research methods, this study collects and analyzes various scientific sources to explain how financial knowledge and understanding contribute to the financial decisions taken by individuals in this age group. The research results show that financial literacy has a significant role in shaping millennial financial behavior. Millennials who have a high level of financial literacy are more likely to manage their income, expenses, savings and investments more effectively. They are also better able to avoid and manage debt wisely and plan long-term finances, including preparing emergency funds and retirement. In addition, good financial literacy can reduce the level of stress or anxiety related to finances among millennials, because they feel more confident in making smart financial decisions. This research underlines the importance of financial education programs that are enhanced and supported by various parties, including educational institutions, government and non-profit organizations, to increase financial literacy among the millennial generation. In conclusion, increasing financial literacy is a key strategy to improve personal financial management among millennials, which in turn can contribute to their financial stability and well-being. These findings are relevant for policy makers and practitioners working to support the development of the financial capacity of the millennial generation.